2010
DOI: 10.1371/journal.pone.0015385
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quantum Yield of Thioflavin T in Rigid Isotropic Solution and Incorporated into the Amyloid Fibrils

Abstract: In this work, the fluorescence of thioflavin T (ThT) was studied in a wide range of viscosity and temperature. It was shown that ThT fluorescence quantum yield varies from 0.0001 in water at room temperature to 0.28 in rigid isotropic solution (T/η→0). The deviation of the fluorescence quantum yield from unity in rigid isotropic solution suggests that fluorescence quantum yield depends not only on the ultra-fast oscillation of ThT fragments relative to each other in an excited state as was suggested earlier, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
156
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 40 publications
12
156
2
Order By: Relevance
“…5). This finding indicated that an increase in the ThT emission The observed emission enhancement phenomenon, induced by the endospore uptake, is consistent with the sensitivity of the photophysical properties of ThT to the viscosity of the environment: i.e., the emission quantum yield of ThT increases with the increase in the medium viscosity (72,74,81,82,88,90). Due to the single carbon-carbon bond between the two ring systems and the single carbon-nitrogen bond between the phenyl ring and the dimethyl amine (Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…5). This finding indicated that an increase in the ThT emission The observed emission enhancement phenomenon, induced by the endospore uptake, is consistent with the sensitivity of the photophysical properties of ThT to the viscosity of the environment: i.e., the emission quantum yield of ThT increases with the increase in the medium viscosity (72,74,81,82,88,90). Due to the single carbon-carbon bond between the two ring systems and the single carbon-nitrogen bond between the phenyl ring and the dimethyl amine (Fig.…”
Section: Resultssupporting
confidence: 77%
“…7). As previously reported, an increase in the medium viscosity causes an increase in the ThT fluorescence quantum yield (82), which is expected given the properties of chromophores, such as ThT, classified as molecular rotors (4,81). A viscosity-induced increase in the emission quantum yield of ThT amounts to about three orders of magnitude (82).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Recently, we have performed super-resolution imaging of fluorescently-stained amyloid fibrils derived from the low pH form of β 2 -microglobulin that is known to be associated with dialysis-related amyloidosis [43]. In our NSOM experiments, we used Nile Red as the fluorescent marker rather than more commonly used ThT due to the following reasons: (i) ThT has also been shown to bind to amorphous protein aggregates owing to the presence of inherent charge [44], (ii) ThT assay at neutral pH cannot be performed to detect amyloid fibrils that are formed at low pH and disintegrate at neutral pH [45], (iii) the low quantum yield of ThT prevents it from being utilized in single-molecule/particle imaging experiments [46] and (iv) ThT exhibits an emission maximum at ~482 nm upon binding to amyloid fibrils and hence, commonly used laser lines such as 488 and 532 nm cannot be used as excitation wavelengths. All these problems can be circumvented if Nile Red is used [47].…”
Section: Applications Of Nsom In Protein Amyloidsmentioning
confidence: 99%